Role of Socio-Economic Status on Adolescents’ Educational Achievement and Adjustment - Singh, Vijay Pratap; Sharma, Sushil Kumar (Journal of Neonatal Surgery, 2025)
The present study examined the relationship of socio-economic status (SES) with educational achievement and adjustment among adolescents. A total of 300 adolescents (150 boys and 150 girls) studying in Classes VIII to X were selected from government high schools of Darbhanga district, Bihar, through purposive sampling. The sample included equal representation from rural and urban areas. Socio-economic status was assessed using the Socio-Economic Status Scale developed by Singh and Saxena, while adjustment was measured using the Adjustment Inventory for School Students (AISS) developed by Sinha and Singh. Educational achievement was determined from the marks obtained by the participants in their most recent annual school examination. Pearson's product-moment correlation coefficient was used to analyze the data. The findings revealed a significant positive relationship between socio-economic status and educational achievement (r = .372, p < .001), indicating that adolescents from higher socio-economic backgrounds tended to achieve better academically. Socio-economic status also showed significant negative correlations with emotional, social, educational and overall adjustment problem scores, suggesting that adolescents with higher socio-economic status were better adjusted than those from lower socio-economic backgrounds. The study concludes that socio-economic status is an important factor influencing both academic performance and psychosocial adjustment during adolescence. The findings underscore the need for educational and social interventions aimed at minimizing socio-economic disparities and promoting the holistic development of adolescents....